Distributed design teams : embedded one-on-one conversations in one-to-many - Larsson, Andreas; Törlind, Peter; Mabogunje, Ade; Milne, Andrew (Luleå tekniska universitet, Innovation och Design, 2002)
Engineering design is fundamentally social, requiring a lot of interaction and communication between the people involved. Additionally, good design often relies upon the ability of a cross-functional team to create a shared understanding of the task, the process and the respective roles of its members. The negotiation and bargaining for common ground are essential in the design process. It is important to provide tools and methods so that also geographically distributed design teams are given the opportunity to engage in such social interactions. This paper presents a study of interpersonal communication within the Distributed Team Innovation (DTI) framework; a joint product design project between Luleå University of Technology and Stanford University that investigates the future of collaborative product development. The common object of work is to design "Virtual Pedals" for Volvo Car Corporation.In the study, we noticed that one-on-one conversations, held in parallel to a main discussion, were common in co-located teamwork and that they are a natural part of creative teamwork. These conversations were mainly used to clarify things and to discuss vague ideas or personal disagreements. Additionally, they were often used instead of, or as a precursor to, bringing up a topic with the whole group. In distributed meetings side conversations were discouraged and current systems for distributed collaboration could not provide sufficient support for these subtle interactions. This has important implications for supporting and improving the performance of global teams, and it suggests that the one-to-many channel of today's video conferencing technology is severely limiting. Godkänd; 2002; 20070328 (petert)